TINJAUAN YURIDIS TERHADAP PERSEKONGKOLAN TENDER BERDASARKAN PASAL 22 UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Lisca Vontya Arifin; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Bid rigging stipulated in Article 22 of the Anti Monopoly Law. The contents of the article as follows : Business agents are prohibited from conspiring with others to organize and / or determine the winner of the tender so as to result in unfair competition. Bid rigging in the procurement of goods / services can be made between the organizers of the tender with the provider of the goods / services and can be done by other bidders. Bid rigging is one form of action that is prohibited by the antitrust laws as bid rigging is fraudulent and harmful acts primarily other bidders who do not participate in cahoots, because by itself in the tender winner can not be arranged, but who do best deals and besides he was the winner bid rigging is anti-competitive actions.With so many cases of bid rigging that goes to the Business Competition Supervisory Commission ( KPPU ), the authors are interested in researching what causes frequent occurrence of bid rigging and how to prevent it. Because we know that there has been no regulation and law governing the conspiracy in the procurement of goods and services, but there are still businesses that do bid rigging. This is where the author wants to know what the actual cause of the frequent occurrence of bid rigging itself. So the authors use normative juridical method in conducting the research thesis.The purpose of this study was to determine the cause of conspiracy in the procurement of goods and services and to determine preventive measures conspiracy in the procurement of goods and services. The results of this study indicate that the cause of the frequent occurrence of bid rigging can be caused by various parties. From law enforcement, the businesses themselves or of the tender committee. And to prevent bid rigging Commission has made electronic auction system through the Electronic Procurement Service ( LPSE ). Where the presence of this LPSEs businesses and tender committee no longer meet.Keywords : Abuse, Conspiracy, Tender